Aqueous zinc ion battery and its electrolyte
By adding glucomannan to the electrolyte of an aqueous zinc ion battery, the problems of insufficient low-temperature and fast-charging performance are solved, and the stability and fast-charging performance of the battery are achieved both in the low-temperature conditions.
Patent Information
- Application Number
- CN202411898367.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-23
AI Technical Summary
Water-based zinc ion batteries have insufficient performance under low temperature and fast charging conditions, making it difficult to take into account both low temperature and fast charging performance.
The electrolyte containing glucomannan as an additive is used to improve the freezing resistance and conduction performance of the electrolyte by controlling its average molecular weight and additive content, thereby improving the low-temperature and fast charging performance.
It significantly improves the low-temperature performance of aqueous zinc ion batteries, takes into account fast charging performance, extends the service life of the battery, and improves the chemical stability of the electrolyte.
Smart Images

Figure CN119361861B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion batteries, and particularly relates to the field of aqueous zinc ion battery electrolytes. Background Art
[0002] With the rapid development of renewable energy, energy storage technology has become the key to solving energy instability. Aqueous zinc-ion batteries have attracted much attention due to their high energy density, low cost and relative environmental protection. This type of battery uses zinc as the negative electrode material and stores energy by transferring electrons between the two plates of the battery through zinc ions. However, aqueous zinc-ion batteries face some problems during long-term use, one of the main problems is the stability of the electrolyte. Additives in the electrolyte play a vital role in the electrochemical reaction and can regulate the performance and life of the battery.
[0003] For example, a Chinese patent document with publication number CN118281367A discloses an aqueous electrolyte with an organic ether polymer added. A Chinese patent document with publication number CN115332646A discloses an electrolyte for a high-temperature safe aqueous zinc ion secondary battery, wherein the electrolyte comprises a zinc-containing electrolyte salt, water and an additive; the additive is an organic small molecule compound, a polymer compound or a specific metal salt that is completely or partially soluble in water, and further records that the additive is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, trimethyl phosphate, triethyl phosphate, hexamethylphosphoric acid triamide, 1,5-pentanediol, glucose, urea, polyethylene oxide, polyethylene glycol, polyvinyl alcohol, polyacrylamide, zinc fluoride, potassium sulfate, potassium hexafluorophosphate, potassium bis(trifluoromethanesulfonyl)imide, potassium bis(trifluoromethanesulfonyl)imide, sodium polyacrylate and sodium hyaluronate.
[0004] In summary, there are some modified electrolytes with added polymers in the prior art, but the existing methods are difficult to effectively improve the low temperature, fast charging and other performances of aqueous zinc batteries. Summary of the invention
[0005] In view of the problem that existing aqueous zinc ion battery electrolytes are difficult to adapt to low temperature and fast charging application requirements, the first purpose of the present invention is to provide an electrolyte for an aqueous zinc ion battery to improve its low temperature and fast charging performance.
[0006] The second purpose of the present invention is to provide the preparation and application of the electrolyte.
[0007] The third object of the present invention is to provide an aqueous zinc ion battery comprising the electrolyte.
[0008] Aqueous zinc batteries are prone to freezing at low temperatures, which affects the conduction of ions and electrons and is difficult to adapt to low-temperature application requirements. Although the prior art has proposed some solutions for low-temperature performance by adding inorganic salts, organic hydrophilic solvents, etc., the low-temperature performance of these solutions still needs to be improved, and it is still difficult to achieve both low-temperature and fast-charging performance. In response to this problem, the present invention has developed the following solutions after in-depth research:
[0009] The electrolyte of the aqueous zinc ion battery is an aqueous solution containing zinc salt and additives; the additives include additive A, wherein the additive A is glucomannan with an average molecular weight of 200,000 to 2 million Daltons;
[0010] In the electrolyte, the content of the additive is 0.01-0.2 wt.%.
[0011] The present invention innovatively adds glucomannan additive A to the aqueous electrolyte, and through the joint control of its average molecular weight and the additive content, it can significantly improve the antifreeze property of the aqueous electrolyte, reduce the ion and electron conduction impedance at low temperatures, and optimize the conduction pathway at low temperatures, which can significantly improve its low-temperature performance. In addition, it can also achieve a good balance between low temperature and fast charging performance.
[0012] The additives described in the present invention can improve the chemical stability of the electrolyte in a wider operating temperature window, reduce the corrosiveness of the reaction products to the battery materials, enhance the low temperature resistance of the aqueous electrolyte, thereby expanding the application temperature range of the electrolyte and extending the service life of the battery.
[0013] In the present invention, the additive further comprises an additive B; the additive B comprises mannan with an average molecular weight of 10,000 to 150,000 Daltons, and can further be mannan with an average molecular weight of 50,000 to 120,000 Daltons. The present invention shows that the combination of the relatively high molecular weight (additive A) and the low molecular weight mannan (additive B) can further optimize its stability at low temperatures and the ion and electron conduction pathway, which helps to further enhance the low temperature fast charging performance of the electrolyte.
[0014] Among the additives, the weight ratio of the additive A to the additive B is 5-20:1.
[0015] The present invention also shows that the additives further include additive C, and the additive C includes at least one of polyethylene glycol, chitosan, polyacrylamide, sodium carboxymethyl cellulose, and gelatin; more preferably polyethylene glycol. The present invention also shows that further adding additive C to the electrolyte helps to further optimize the network structure and helps to further enhance the low temperature, fast charging and other properties of the electrolyte.
[0016] In the present invention, the average molecular weight of the additive C is 10,000 to 100,000 Daltons; further, it can be 10,000 to 50,000 Daltons.
[0017] Among the additives, the weight ratio of the additive A to the additive C is 5-20:1.
[0018] Furthermore, in the additives, the content of the additive A is above 50 wt %, and can further be above 80 wt %.
[0019] In a preferred embodiment of the present invention, the additive comprises additive A and additive B, wherein additive A accounts for 85-95wt% of the additive, and the remainder is additive B. In a further preferred embodiment of the present invention, the additive comprises additive A, additive B and additive C, wherein the content of additive A is 85-90wt%; additive B is 3-6wt%; and the remainder is additive C.
[0020] In the present invention, the zinc salt is at least one of zinc sulfate, zinc chloride, zinc acetate, zinc trifluoromethanesulfonate, manganese acetate, and manganese sulfate; more preferably zinc sulfate. Studies have shown that the use of the preferred zinc salt, combined with the additives and parameters of the present invention, can obtain better network conduction capacity and better low-temperature fast charging performance.
[0021] In the present invention, in the electrolyte, the concentration of zinc salt is 0.5-5M, and can further be 1-3M.
[0022] In the electrolyte, the content of the additive is 0.02-0.1 wt.%, and more preferably 0.02-0.04 wt.%. Studies have shown that the combination of the additive and its parameters, and further control of the amount of addition, can further synergize and help further optimize the conduction network and improve low-temperature performance. In addition, it also takes into account excellent fast charging performance.
[0023] The invention also provides a method for preparing the electrolyte, which is obtained by uniformly mixing the components.
[0024] The present invention also provides application of the electrolyte of the aqueous zinc ion battery, which is used as the electrolyte to prepare the aqueous zinc ion battery.
[0025] The present invention also provides an aqueous zinc ion battery, comprising a battery core and an electrolyte for soaking the battery core, wherein the battery core comprises a positive electrode, a diaphragm and a negative electrode which are composited in sequence, and the electrolyte comprises the electrolyte of the present invention.
[0026] The aqueous zinc ion battery, in addition to the electrolyte described in the present invention, may have other components and structural features that are known or reasonably controlled based on known principles.
[0027] For example, the active material of the positive electrode includes at least one of a manganese-based material, a vanadium-based material, and Prussian blue.
[0028] The negative electrode includes a flaky zinc negative electrode active material.
[0029] The diaphragm is glass fiber.
[0030] Beneficial Effects
[0031] The present invention uses an additive A with a super-large molecular weight of 200,000 to 2 million Daltons as an additive to the electrolyte. It acts as both a hydrogen bond breaker and a zinc ion coordinator, and has a unique dual function. It can significantly improve the antifreeze property of the aqueous electrolyte, reduce the ion and electron conduction impedance at low temperatures, and optimize the conduction pathway at low temperatures, thereby significantly improving its low-temperature performance. In addition, it can also achieve a good balance between low temperature and fast charging performance. In the present invention, the low temperature and fast charging performance of the electrolyte can be further enhanced by jointly controlling the additive A and the amount of addition. For example, an aqueous zinc symmetrical battery at 25°C with a current density of 7mA / cm 2 (mA / cm 2 Also reported as mA cm -2 ) and capacity 3.5mAh / cm 2 (mAh / cm 2 Also reported as mAh cm -2 ) can cycle for 3510 hours; at -10℃, with a current density of 5mA / cm 2 and capacity 2.5mAh / cm 2 In aqueous zinc-ion full batteries, at 25°C, the current density is 15A / g (A / g is also recorded as Ag -1 ) and the retention rate was still 81% after 7500 cycles. At -10℃, it can stably cycle for more than 1100 cycles at a current density of 2A / g.
[0032] In addition, the study also shows that the use of a combination additive including additive A can further achieve synergy based on the adaptive combination of additives and parameters such as molecular weight, and can further enhance the low temperature and fast charging performance of the electrolyte. The preparation method of the electrolyte with the additive provided by the present invention is simple, efficient, and low-cost, which is conducive to the industrial application of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The DSC graphs of the electrolyte of Example 1 (marked as 0.025% KGM) and the electrolyte of Comparative Example 1 (marked as w / o KGM);
[0034] Figure 2 Symmetrical cells assembled with the electrolyte of Example 1 (labeled as 0.025% KGM) and the electrolyte of Comparative Example 1 (labeled as w / o KGM) at -10°C and 0.5 mA / cm 2 -0.25mAh / cm 2 Lower cycle diagram;
[0035] Figure 3 The graph is a test result of hydrogen evolution corrosion of zinc negative electrode of the electrolyte of Example 1 (marked as 0.025% KGM) and the electrolyte of Comparative Example 1 (marked as w / o KGM);
[0036] Figure 4 Symmetric cells containing electrolytes of Example 1 (labeled as 0.025% KGM) and electrolytes of Comparative Example 1 (labeled as w / o KGM) were run at a current density of 1 mA / cm at 25°C. 2 and capacity 0.5mAh / cm 2 XRD patterns of the zinc anode after 200 h of cycling and the original zinc anode;
[0037] Figure 5 The cycle diagram of the full battery assembled with the electrolyte of Example 1 (marked as 0.025% KGM) and the electrolyte of Comparative Example 1 (marked as w / o KGM) at room temperature -10°C and 1A / g.
[0038] Figure 6 The symmetrical battery assembled with the electrolyte of Example 2 was heated at 25°C and 1 mA / cm 2 -0.5mAh / cm 2 The following cycle diagram. DETAILED DESCRIPTION
[0039] The present invention is further described in detail in conjunction with the following examples and drawings, but the embodiments of the present invention are not limited thereto.
[0040] The present invention can prepare the electrolyte based on a conventional mixing method, for example, the optional steps are:
[0041] (1) Calculate the required mass of zinc sulfate based on the required concentration and volume of zinc sulfate solution, and calculate the required mass of additives.
[0042] (2) Use an electronic balance to weigh zinc sulfate, add the weighed zinc sulfate into a beaker, add deionized water, stir with a magnetic stirrer at a speed of 1000-1200 r / min, and heat in a water bath at 40-60°C until the zinc sulfate is completely dissolved.
[0043] (3) Weigh the additive using an electronic balance; slowly add the additive to the zinc sulfate solution and continue stirring until the additive is completely dispersed.
[0044] (4) Transfer the dissolved zinc sulfate and additive solution to a volumetric flask; rinse the beaker with a small amount of deionized water to ensure that all the solution is transferred to the volumetric flask. Continue to add deionized water to the volumetric flask until the volume of the solution reaches the scale line, and finally use a dropper to accurately adjust to ensure the accurate volume of the solution. Cover the volumetric flask, gently shake or rotate the bottle to ensure that the solution is evenly mixed and that there is no obvious suspended matter or precipitation in the solution to obtain the electrolyte.
[0045] In the present invention, the cycle time of the symmetrical battery refers to the cycle time of short circuit or near short circuit.
[0046] Example 1
[0047] Electrolyte: The additive is Additive A, which is glucomannan with an average molecular weight of 500,000 Daltons; wherein the concentration of zinc salt (zinc sulfate in this case) is 2M, and the overall additive accounts for 0.025% of the electrolyte mass content.
[0048] Test method: Use an electrochemical workstation with a scan rate of 0.1 mV s -1 Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) measurements were performed from 0.1 to 105 Hz. Tafel tests were performed on an electrochemical workstation at 50 mV s -1 The chronoamperometry (CA) was performed at a continuous overpotential of -150 mV using a Zn / / Zn symmetric cell. The CV and cycling performance of the Zn / / V2O5 full cell at different current densities from 0.2 to 1.8 V were studied. All the above electrochemical measurements were performed on a NEWARE MIHW-200-160CH-B battery test system. Linear sweep voltammetry (LSV) was performed on a DH7000 electrochemical workstation at 10 mV s -1 The scan rate is performed.
[0049] The specific battery assembly method is as follows:
[0050] Cut the negative electrode sheet into a disc with a diameter of 12mm, and the positive electrode sheet into a disc with a diameter of 10mm. Assemble the battery in the order of positive electrode shell, positive electrode disc, diaphragm, negative electrode disc, gasket, spring, and negative electrode shell. The positive electrode disc and negative electrode disc are required to be placed in the center, and a diaphragm (glass fiber) is arranged between the positive and negative electrodes. After placing the diaphragm, drip an appropriate amount of electrolyte to ensure that the diaphragm is completely wetted. The positive electrode disc is replaced by the negative electrode disc to form a symmetrical battery. Finally, press and wipe the electrolyte on the surface of the battery on a fully automatic button battery press. In the symmetrical battery, the positive electrode is a copper sheet with a diameter of 12mm. In the full battery, the positive electrode is V 2 O 5, including a stainless steel mesh and a V coated 2 O 5 , where V 2 O 5 The mass loading was 2.5 mg cm -2 , assemble 2025 type button zinc ion battery. The electrochemical performance of the prepared battery was tested using an electrochemical workstation, and the results were:
[0051] The prepared electrolyte was used in a symmetrical cell at a current density of 1 mA / cm 2 and capacity 0.5mAh / cm 2 It can cycle for 60-60 hours.
[0052] The prepared electrolyte was used in a symmetrical cell at a current density of 3 mA / cm 2 and capacity 1.5mAh / cm 2 It can cycle nearly 5000 hours.
[0053] The prepared electrolyte was used in a symmetrical cell at a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 It can cycle for nearly 1250 hours.
[0054] The prepared electrolyte was used in a symmetrical cell at a current density of 0.5 mA / cm 2 and capacity 0.25mAh / cm 2 It can cycle for nearly 7250 hours.
[0055] At -10 °C, the prepared electrolyte symmetric cell was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 1040 hours.
[0056] At -10 °C, the prepared electrolyte maintained a 99% retention rate after 1100 cycles at a current density of 2 A / g in a full battery.
[0057] At 25°C, the prepared electrolyte retained 81% after 7500 cycles at a current density of 15 A / g in a full battery.
[0058] At -10 °C, the prepared electrolyte was cycled 2000 times at a current density of 1 A / g in a full battery with a retention rate of 99.1%.
[0059] Embodiment 2:
[0060] Compared with Example 1, the only difference is that the amount of glucomannan added in the electrolyte is changed, and the other operations and parameters are the same as Example 1. The experimental groups are:
[0061] (1) Group: The content of additives in the electrolyte is 0.01wt%;
[0062] (2) Group: The content of additives in the electrolyte is 0.1wt%;
[0063] (3) Group: the content of additives in the electrolyte is 0.2wt%;
[0064] Tested according to the method of Example 1, the results are:
[0065] (1) Group: The prepared electrolyte was charged in a symmetrical cell at a current density of 1 mA / cm at 25 °C. 2 and capacity 0.5mAh / cm 2 It can cycle for nearly 1657 hours at a current density of 3mA / cm 2 and capacity 1.5mAh / cm 2 It can circulate for nearly 968 hours.
[0066] At -10 °C, the prepared electrolyte symmetric cell was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 260 hours.
[0067] (2) Group: The prepared electrolyte was charged in a symmetrical cell at a current density of 1 mA / cm at 25 °C. 2 and capacity 0.5mAh / cm 2 It can cycle for nearly 2889 hours at a current density of 3mA / cm 2 and capacity 1.5mAh / cm 2 It can circulate for nearly 852 hours.
[0068] At -10 °C, the prepared electrolyte symmetric cell was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 320 hours.
[0069] (3) Group: The prepared electrolyte was charged in a symmetrical cell at a current density of 1 mA / cm at 25 °C. 2 and capacity 0.5mAh / cm 2 It can cycle for nearly 2899 hours at a current density of 3mA / cm 2 and capacity 1.5mAh / cm 2 It can circulate for nearly 589 hours.
[0070] At -10 °C, the prepared electrolyte symmetric cell was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 360 hours.
[0071] It can be seen from Examples 1 and 2 that the combined control of the dosage of additives, especially controlling the dosage of additives to 0.02~0.04wt.%, can unexpectedly construct a dual-phase electrolyte system, which can significantly optimize the fast charging and low temperature performance of the battery.
[0072] Example 3
[0073] Compared with Example 1, the only difference is that the molecular weight of the glucomannan in additive A is controlled to 1 million Daltons, and the other operations and parameters are the same as those in Example 1. The test is carried out according to the method of Example 1, and the results are:
[0074] The prepared electrolyte was used in a symmetrical cell at a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 It can cycle for nearly 1150 hours.
[0075] At -10 °C, the prepared electrolyte symmetric cell was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 970 hours.
[0076] Example 4
[0077] Compared with Example 1, the only difference is that the additives of the electrolyte include additive A and additive B, wherein additive A is glucomannan with an average molecular weight of 500,000 Daltons; additive B is mannan (additive B) with an average molecular weight of 100,000 Daltons; and among the additives, the content of additive A is 90 wt.%, and the total additive dosage and other operations and parameters are consistent with Example 1.
[0078] At 25°C, the electrolyte containing the prepared additive was subjected to a current density of 1 mA / cm 2 and capacity 0.5mAh / cm 2 The prepared electrolyte can be cycled for more than 7800 hours (referring to 7800 hours without short circuit failure). At 25°C, the prepared electrolyte can be cycled for more than 7800 hours (referring to 7800 hours without short circuit failure) in a symmetrical battery with a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 It can cycle for nearly 3050 hours.
[0079] The prepared electrolyte with additives was used in a symmetrical cell at a current density of 5 mA / cm2 and capacity 2.5mAh / cm 2 It can circulate for nearly 2205 hours.
[0080] It can be seen from Examples 1 and 4 that the use of the additives in combination of Additive A and Additive B, further coordinated with the joint control of their molecular weights, can help to further construct a battery-compatible dual-phase electrolyte, which can achieve better fast charging and low-temperature performance.
[0081] Example 5
[0082] Compared with Example 4, the only difference is that the additives in the electrolyte include additives A, B and C, and additive C is polyethylene glycol with an average molecular weight of 20,000 Daltons (additive C); and among the additives, the content of additive A is 90Wt.%, the contents of additives B and additive C are each 5Wt.%, and the amount of additives and other operations and parameters are consistent with Example 1.
[0083] At 25°C, the electrolyte containing the prepared additive was used in a symmetrical cell at a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 It can cycle for 3510 hours.
[0084] The prepared electrolyte with additives was used in a symmetrical cell at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 2560 hours.
[0085] It can be seen from Examples 4 and 5 that the use of a combination of Additive A, Additive B and Additive C helps to further construct an electrolyte network structure, which can achieve better fast charging and low temperature performance.
[0086] Example 6
[0087] Compared with Example 1, the only difference is that the zinc salt is replaced by ZnCl2; other operations and parameters are the same as in Example 1.
[0088] The test was carried out according to the method of Example 1. The results were as follows: at 25°C, the electrolyte containing the prepared additive had a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 The electrolyte with the prepared additive can be cycled for nearly 830 hours at -10°C in a symmetrical cell with a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 560 hours.
[0089] It can be seen from Examples 1 and 6 that zinc sulfate is used as the zinc salt, which has better compatibility with the additives described in the present invention, and can obtain better low-temperature and fast-charging performance.
[0090] Example 7
[0091] Compared with Example 1, the only difference is that the concentration of the zinc salt is 1.5 M; other operations and parameters are the same as in Example 1.
[0092] The test was carried out according to the method of Example 1. The results were as follows: at 25°C, the electrolyte containing the prepared additive had a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 The electrolyte with the prepared additive can be cycled for nearly 1152 hours at -10°C in a symmetrical cell with a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 985 hours.
[0093] Comparative Example 1
[0094] Compared with Example 1, the only difference is that the additive is not added to the electrolyte. The test is carried out in the manner of Example 1, and the results are:
[0095] At 25°C, the prepared symmetric battery was charged at a current density of 1 mA / cm 2 and capacity 0.5mAh / cm 2 It can circulate for nearly 376 hours.
[0096] At 25 °C, the prepared symmetric battery was charged at a current density of 3 mA / cm 2 and capacity 1.5mAh / cm 2 It can circulate for nearly 215 hours.
[0097] At -10 °C, the prepared symmetric battery was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 The next cycle is 17 hours.
[0098] At -10°C, the prepared full battery can be cycled 250 times (failure) at a current density of 1A / g.
[0099] Comparative Example 2
[0100] Compared with Example 1, the only difference is that the additive B (mannan) of Example 4 is used as the only additive, and the total amount of the additive and other operations and tests are the same as those of Example 1. The results are:
[0101] At 25°C, the prepared symmetric battery has a current of 7 mA / cm2 and capacity 3.5mAh / cm 2 It can cycle for 612 hours.
[0102] At -10 °C, the prepared symmetric battery was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 It can cycle for nearly 230 hours.
[0103] Comparative Example 3
[0104] Compared with Example 1, the only difference is that the polyvinyl alcohol (PVA) of Example 5 is used to replace the additive A shown as the only additive, and the total amount of the additive and other operations and tests are the same as in Example 1. The results are:
[0105] At 25 °C, the prepared symmetric battery has a current density of 7 mA / cm 2 and capacity 3.5mAh / cm 2 It can cycle for 315 hours.
[0106] At -10 °C, the prepared symmetric battery was charged at a current density of 5 mA / cm 2 and capacity 2.5mAh / cm 2 The next cycle lasts nearly 50 hours.
Claims
1. The electrolyte of the aqueous zinc ion battery is an aqueous solution containing a zinc salt and an additive; characterized in that: The additive comprises additive A, wherein the additive A is glucomannan having an average molecular weight of 200,000 to 2 million Daltons; In the electrolyte, the content of the additive is 0.02-0.1 wt.%.
2. The electrolyte of the aqueous zinc ion battery according to claim 1, wherein The additives also include additive B; the additive B is mannan with an average molecular weight of 10,000 to 150,000 Daltons.
3. The electrolyte of the aqueous zinc ion battery according to claim 2, wherein Among the additives, the weight ratio of the additive A to the additive B is 5-20:
1.
4. The electrolyte of the aqueous zinc ion battery according to claim 1, wherein The additives further include additive C, and the additive C includes at least one of polyethylene glycol, chitosan, polyacrylamide, sodium carboxymethyl cellulose, and gelatin; The average molecular weight of the additive C is 10,000 to 100,000 Daltons; Among the additives, the weight ratio of the additive A to the additive C is 5-20:
1.
5. The electrolyte of the aqueous zinc ion battery according to any one of claims 1 to 4, characterized in that Among the additives, the content of the additive A is above 50wt%.
6. The electrolyte of the aqueous zinc ion battery according to claim 1, characterized in that The zinc salt is at least one of zinc sulfate, zinc chloride, zinc acetate, zinc trifluoromethanesulfonate, manganese acetate and manganese sulfate.
7. The electrolyte of the aqueous zinc ion battery according to claim 1, characterized in that In the electrolyte, the concentration of zinc salt is 0.5~5M; the content of the additive is 0.02~0.1 wt.%.
8. Use of an electrolyte for an aqueous zinc ion battery according to any one of claims 1 to 7, characterized in that: It is used as an electrolyte to prepare aqueous zinc-ion batteries.
9. An aqueous zinc ion battery, comprising a battery cell and an electrolyte for soaking the battery cell, wherein the battery cell comprises a positive electrode, a separator and a negative electrode which are composited in sequence, characterized in that: The electrolyte comprises the electrolyte according to any one of claims 1 to 7.
10. The aqueous zinc ion battery according to claim 9, characterized in that: The active material in the positive electrode includes at least one of a manganese-based material, a vanadium-based material, and Prussian blue; The negative electrode includes a flaky zinc negative electrode active material; The diaphragm is glass fiber.
Citation Information
Patent Citations
Electrolyte for high-temperature safe aqueous zinc ion secondary battery, and preparation method and application thereof
CN115332646A
Aqueous electrolyte modification method based on organic ether polymer and application of aqueous electrolyte modification method in zinc ion battery
CN118281367A